1, 2, 4‐Oxadiazole‐Bridged Polynitropyrazole Energetic Materials with Enhanced Thermal Stability and Low Sensitivity. Issue 10 (9th October 2019) - Yan, Tingou; Cheng, Guangbin; Yang, Hongwei
Abstract: A family of mono or di(1, 2, 4‐oxadiazole)‐bridged polynitropyrazole derivatives with C ‐nitro/ N ‐nitro functionalities is reported. All compounds were fully characterized by IR, NMR ( 1 H, 13 C), elemental analysis and differential scanning calorimetry (DSC). The solid‐state structure features were further investigated with X‐ray diffraction. Of these, compounds 3, 5‐bis(3, 4‐dinitro‐1H‐pyrazol‐5‐yl)‐1, 2, 4‐oxadiazole (3 a ) and 5, 5′‐bis(3, 4‐dinitro‐1H‐pyrazol‐5‐yl)‐3, 3′‐bi(1, 2, 4‐oxadiazole) (3 b ) possess high thermal stability (3 a : T dec =274 °C; 3 b : T dec =272 °C), sensitivity ( IS >30 J, FS >360 N) and comparable detonation properties (3 a : D v =8741 m s −1, P =34.0 GPa; 3 b : D v =8685 m s −1, P =33.4 Gpa) to RDX. In addition, 3, 5‐bis(4‐nitro‐1H‐pyrazol‐3‐yl)‐1, 2, 4‐oxadiazole (4 a ) and 5, 5′‐bis(4‐nitro‐1H‐pyrazol‐3‐yl)‐3, 3′‐bi(1, 2, 4‐oxadiazole) (4 b ) have high decomposition temperature (4 a : T dec =314 °C; 4 b : T dec =317 °C), low sensitivity ( IS >40 J; FS >360 N) and superior detonation performances (4 a : D v =8027 m s −1, P =26.4 GPa; 4 b : D v =7991 m s −1, P =25.2 Gpa) than conventional heat‐resistant explosive hexanitrostilbene (HNS: T dec =318 °C; IS =5 J; FS =240 N; D v =7612 m s −1, P =24.3 GPa), thus suggesting their potential application as heat‐resistant explosives. Abstract : Stable and resistant : A family of mono‐ and di(1, 2, 4‐oxadiazole)‐bridged polynitropyrazole energetic materials was designed and synthesized. These compounds exhibit excellent thermal stability and good detonation properties, as well as low sensitivity. By varying the number of energetic C ‐nitro groups on the polynitropyrazole rings, different classes of energetic materials including heat‐resistant explosives and high‐performance secondary explosives were obtained.